In vivo characterization and numerical simulation of prostate properties for non‐thermal irreversible electroporation ablation. Issue 5 (17th January 2014) - Neal, Robert E; Millar, Jeremy L; Kavnoudias, Helen; Royce, Peter; Rosenfeldt, Franklin; Pham, Alan; Smith, Ryan; Davalos, Rafael V; Thomson, Kenneth R
ABSTRACT BACKGROUND Irreversible electroporation (IRE) delivers brief electric pulses to attain non‐thermal focal ablation that spares vasculature and other sensitive systems. It is a promising prostate cancer treatment due to sparing of the tissues associated with morbidity risk from conventional therapies. IRE effects depend on electric field strength and tissue properties. These characteristics are organ‐dependent, affecting IRE treatment outcomes. This study characterizes the relevant properties to improve treatment planning and outcome predictions for IRE prostate cancer treatment. METHODS Clinically relevant IRE pulse protocols were delivered to a healthy canine and two human cancerous prostates while measuring electrical parameters to determine tissue characteristics for predictive treatment simulations. Prostates were resected 5 hr, 3 weeks, and 4 weeks post‐IRE. Lesions were correlated with numerical simulations to determine an effective prostate lethal IRE electric field threshold. RESULTS Lesions were produced in all subjects. Tissue electrical conductivity increased from 0.284 to 0.927 S/m due to IRE pulses. Numerical simulations show an average effective prostate electric field threshold of 1072 ± 119 V/cm, significantly higher than previously characterized tissues. Histological findings in the human cases show instances of complete tissue necrosis centrally with variable tissue effects beyond the margin. CONCLUSIONS Preliminary experimental IRE trials safely ablated healthy canine and cancerous human prostates, as examined in the short‐ and medium‐term. IRE‐relevant prostate properties are now experimentally and numerically defined. Importantly, the electric field required to kill healthy prostate tissue is substantially higher than previously characterized tissues. These findings can be applied to optimize IRE prostate cancer treatment protocols. Prostate 74:458–468, 2014. © 2014 Wiley Periodicals, Inc.